Development and Characterization of Powdered Antioxidant Compounds Made from Shiraz (Vitis vinifera L.) Grape Peels and Arrowroot (Maranta arundinacea L.) - Euzélia Lima Souza; Talita Sousa Nascimento; Camila Miranda Magalhães; Gabriele de Abreu Barreto; Ingrid Lessa Leal; Jeancarlo Pereira dos Anjos; Bruna Aparecida Souza Machado (The Scientific World Journal)
Grapevine (Vitis vinifera L.) is a plant containing many phenolic compounds, mostly distributed in the peel, pulp, and seeds. This study evaluates the centesimal composition and bioactive compounds in Shiraz grape (Vitis vinifera) peels using spectrophotometric and UHPLC techniques and develops different formulations of compound powders from the peels and arrowroot using conventional drying technology. The results demonstrate that Shiraz grape skin contains significant amounts of insoluble fiber (15.3%), phenolics (157.09 ± 6.96–149.11 ± 9.27 mg GAE g−1), and flavonoids (0.75 ± 0.50–2.00 ± 0.50 mg QE g−1), with excellent antioxidant capacity observed in the alcoholic extracts. The phenolic content in the developed powdered compounds ranged from 128.32 to 139.70 mg GAE g−1. In general, the compounds showed good antioxidant capacity (IC50 = 0.17 to 0.19 μg mL−1). According to the chromatographic evaluation, it was possible to quantify gallic acid, catechin, and epicatechin, the latter of which was found in the largest quantities in the six formulations. The EV5 formulation was the most efficient in terms of phenolic compounds and protein amounts. This formulation’s composition and low cost could make it viable for use in the food industry.